RESPONSIVE GOVERNANCE DALAM PENANGANAN ADUAN MASYARAKAT MELALUI PORTAL LAPORGUB BALAI BESAR PELAKSANAAN JALAN NASIONAL (BBPJN) JAWA TENGAH- DAERAH ISTIMEWA YOGYAKARTA - Reina Tri Lenggani; R. Slamet Santoso (Journal of Management and Public Policy, 2026)
Public complaint handling is an important indicator in realizing responsive governance. Governments are required to respond to public complaints promptly, accurately, and carefully as a form of citizen-oriented public service. This study aims to analyze the implementation of responsive governance in handling public complaints through the LaporGub! Portal at the National Road Implementation Agency of Central Java–Special Region of Yogyakarta (BBPJN Central Java–DIY) and to identify the inhibiting factors. This research employs a qualitative descriptive method with data collection techniques consisting of in-depth interviews, observations, and documentation. The informants include BBPJN Central Java–DIY officials and related stakeholders involved in complaint management. The findings show that the implementation of responsive governance has been carried out through the utilization of a digital complaint system, particularly in initial responses and report distribution mechanisms. However, the responsiveness demonstrated remains administrative in nature and has not fully focused on substantive problem resolution. The main inhibiting factors include limited human resources, insufficient budget allocation, and lengthy internal bureaucratic processes. This study concludes that improving responsiveness should emphasize follow-up certainty, bureaucratic efficiency, and the substantive fulfillment of public needs.